Effects of vertical versus horizontal plyometric training on adolescent soccer players` physical performance - Bogiatzidis, E.; Ispyrlidis, I.; Gourgoulis, V.; Bogiatzidis, A. (Trends in Sport Sciences, 2024)
Introduction: Plyometric training has become a popular training method of youth soccer players. Researchers have sought to use different forms of training to maximize performance responses.